KEBIJAKAN HUKUM PIDANA TERHADAP TINDAK PIDANA PEMERKOSAAN ANAK DIBAWAH UMUR (Studi Putusan Pengadilan Negeri Rantauprapat No.694/Pid.Sus/2016/PN-Rap) - Faisal Salim Putra Ritonga; Syafruddin Kalo; Madiasa Ablisar; Marlina Marlina (Universitas Sumatera Utara, 2018)
ABSTRACT Based on the provisions of article 1 point 1 of the Act No.23 of 2003 Year shield cover Children Jo article 1 1 of the Act No. 35 year 2014 about changes in the law No.23 of the year 2003 on the protection of the child, which States that the child is someone who has not aged 18 (eighteen) years of age, including children who are still in the womb. Children as subjects of law who are immature (human) does not cover the possibility of getting involved with the law, which means that a child can be the subject or object of the law in a legal events. One of the issues of concern to children is a special case of rape. Rape is a type of crime that affects very bad especially on victims, for rape would violate human rights and may damage the dignity of humanity, especially against the soul, reason and offspring. One of his Ruling State Court matter Rantauprapat matter No.694/Pid.Sus/2016/PN-Rap is something rape against children under age. In this case the occurrence of criminal offence deliberately doing hokey pokey, a series of lies or persuading a child do it. The defendant committing criminal acts against children under age (15 years) with doing serangakian lies with persuading the victim to perform coitus. Policy formulation of the law of criminal offence rape of children under based on the provisions of article 81 paragraph (2) of Act No.35 year 2014 about changes in the Law No.23 of the year 2003 on the protection of Children and the law On article 290 of the criminal clause (2) and (3), article 292, 293, article 294 Article paragraph (1) and section 295. The application of the criminal law against the crime of rape children under based on the ruling of the District Court Rantauprapat No.694/Pid.Sus/2016/PN-Rap based on article 81 paragraph (2) and the provisions of article 76 d. consideration of judge against based on the verdict of the District Court Rantauprapat No.694/Pid. Sus/2016/PN-Rap has not been fullest to suppress the occurrence of cases of abuse and permerkosaan minors. Judges in meting out criminal prison to the defendant should have maximum as in the provisions of article 81 paragraph (2) and the provisions of article 76 D Act No.35 year 2014 about changes in the Law No.23 of the year 2003 on the protection of The child. Recommended for law enforcement gives the application of criminal law in state court verdict Rantauprapat No.694/Pid.Sus/2016/PN-Rap in accordance with the criminal law policy contained in the provisions of Act No.35 year 2014 about changes top of Act No.23 of year 2003 on the protection of Children so that the existence of a deterrent effect for the accused and legal certainty for the victims. Keywords : legal policy, crime, rape, minors,